Psychotropic drug use as indicator of mental health in adolescents affected by a plexus injury at birth : A large population-based study in Sweden - Psouni, Elia ; 0000-0003-2758-5785; Perez Vicente, Raquel; Dahlin, Lars B ; 0000-0003-1334-3099; Merlo, Juan ; 0000-0001-8379-9708 (PLoS ONE, 2018)
Chronic handicap in early life may have a long-term impact on children's psychosocial well-being. Here, we investigated whether Brachialis Plexus Birth Injury (BPBI)-an unpredictable injury at birth-is associated with worse mental health later on, as indicated by prescription and use of psychotropic drugs in adolescence. We explored further whether this association is different depending on socioeconomic characteristics of the child's family, as well as sex. Of the 641 151 children born to native parents in Sweden 1987-1993 (alive and still living in Sweden at the end of 2008), identified in the Swedish Medical Birth Registry, 1587 had suffered a BPBI. Logistic regression analysis was performed to assess the impact of socioeconomic characteristics and associations with later psychosocial health. Results show that beyond the known increased risks for females as compared to males, BPBI, but also lower family income, further increased the risk of burdened mental health requiring psychotropic drug use in adolescence. The effects were additive. Thus, compared to unaffected peers, teenagers who suffered a BPBI at birth are at higher risk of suffering poor mental health during adolescence, independently of surgical intervention and its outcome. Girls growing up in families with lower socioeconomic status have this risk added to their already increased risk of poor mental health during adolescence.